Adaptive state observers for sensorless control of switched reluctance motors. (28th November 2018) - Ortega, R.; Sarr, A.; Bobtsov, A.; Bahri, I.; Diallo, D.
Summary: In this paper, we address the problem of state observation for sensorless control of switched reluctance motors (SRMs), that is, the regulation of the motor measuring only the voltage and the current of the electrical supply. Instrumental for the construction of the observer is the derivation of algebraic relations, which define regression models, between the unknown rotor flux and the measured quantities. With the knowledge of the flux, it is shown that the mechanical coordinates can be estimated with suitably tailored adaptive nonlinear observers. Replacing the observed states, in a certainty equivalent manner, with a full information stabilizing law completes the sensorless controller design. In contrast with other motors, there is no universally accepted mathematical model to describe the dynamics of SRMs. To widen our target audience, we present the results for four different mathematical models reported in the literature. Simulation results with a precise (finite element) model of the SRM are used to illustrate the performance of the proposed observer and sensorless control.